Toward improving Sebha University in world universities ranking (Journal of Pure & Applied Sciences, 2019)
The aim of this study is to provide an overview of Webometrics universities ranking which consider as one of the most well-known ranking in Libyan and Arab world universities. Webometrics rank represents how well the university perform based on web impact factor. In this study, several experiments have been conducted to compare the performance of Sebha University against other local and Arab word universities. This study shows the factors responsible for the falling standards of Sebha University rank in webometrics and the lack of local and global recognition of the Libyan universities in webometrics. Moreover, the study presents a recommendation in order to improve Sebha University ranking, which might applied to other Libyan universities.